Studi Kepadatan Jentik Nyamuk di Kelurahan Tebing Tinggi Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat Jambi Tahun 2019 - Sondang Siahaan; Rina Fauziah (Universitas Batanghari Jambi, 2020)
Mosquitoes have a very important meaning in the health sector because of their role as vectors of various diseases. Diseases transmitted by mosquitoes include dengue fever, malaria and filariasis. These three diseases are transmitted from one person to another through vector intermediaries. Vector is a creature that acts as an intermediary for transmitting diseases. Tebing Tinggi Village is a densely populated area. The density of the population as well as the constraints of clean water make a lot of water reservoirs to store daily water needs. This can potentially be a breeding ground for mosquito larvae. This study was conducted to determine the density of mosquito larvae, to find out the percentage of house index and container index. This study used a visual method, with a cross sectional approach. Based on the results of research from 18 houses (19.78%) that were larvae positive from 91 houses examined and found 22 containers (5.78%) positive larvae from 380 containers examined. 331 containers of larvae were found in the reservoir of deep water as much as 18 containers (5.43%) and as many as 49 containers of larvae were found in the external water reservoir (12.24%). The density of mosquito larvae in Tebing Tinggi area is categorized as being with density figures 3 and 4. The amount on the surface of the presence of mosquito larvae in water reservoirs in the house should the community pay more attention to the cleanliness of water reservoirs and to close water storage so that they are not breeding grounds.